UM OLHAR DIDÁTICO SOBRE A GEOMETRIA FINITA - MARCELO COSTA VALERIANO (2024)
This work presents a sequence of activities to provide students with contact with non-Euclidean geometries, specifically finite geometries, as a form of a different proposal for the teaching of geometry in elementary school. For this, at, first the basic concepts of modern geometry are presented, as well as some finite geometries with their main concepts and demonstrations. Then it will be shown what reasons involve the need for a different approach in teaching geometry, as well as the benefits of this approach. ending the last chapter with the proposals of activities, involving both the use of Geoboard to create models of finite geometries that will be presented to students and using the game Dobble for a light introduction to projective spaces, especially finite projective planes.